Religion and the Digital Era 5.0: The Existence of Religion among Millennials and Generation Z - Cindenia Puspasari; Samhudi Samhudi; Darmadi Darmadi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Religion in the digital era presents challenges for education and religious practices for the younger generation in Indonesia. The internet and social media have become the main sources of religious information for many young people, which potentially increases the occurrence of intolerance. To address this, effective religious education strategies are needed, which incorporate technology to engage the digital generation. The goal is to maintain the existence of religion by adapting to changes, developing competencies in digital technology to effectively reach and explore the creativity of the younger generation. Overall, religion continues to play an important role in the digital era, despite new challenges and opportunities. This article refers to the implications of Al Ghazali's theory, Al Ghazali's views on ilm (knowledge) with ta'awun (social cooperation), which can be seen as a form of mutually supportive social networks in Islamic society. As a result, modern thinkers connect Al-Ghazali's thoughts with the dynamics of social and religious relationships in Islam, particularly in observing the phenomenon of religious existence issues among the millennial and Gen Z generations in Indonesia